REFLEKSI EKSISTENSIALISME DALAM ILMU HUKUM (SUATU UPAYA HUMANISASI TERHADAP TEORI ILMU HUKUM) - Hermansyah, Hermansyah (Faculty of Law, Universitas Jenderal Soedirman, 2008)
The existentialism of philosophy has concern and admits the uniqueness of the human being. The effort of the theorititation of law should be back to the good of human being aspect as individual and also the community. Uniforming to the individual thinking in universal term as well as in positivism theory (law) will have given a fence for the human being freedom like represent of the denial in the existing individual variety, so that the existence becoming limited by human meaning. Theory compilation for social fact that perceived have peep out the regular nature, it is representing just a few of the human being side that have the richness of value. Kata Kunci: humanisme, alienasi, eksistensialisme, ilmu hukum